CODE MIXING FOUND IN THE OFFICIAL TWITTER OF BKN (INDONESIA NATIONAL CIVIL SERVICE AGENCY) - Mohamad Syihabuddin Faqih (STKIP PGRI Jombang, 2022)
This research aims to investigate the types and factors of code mixing which found in the official twitter account of BKN (Indonesia National Civil Service Agency) during the registration of civil servant’s candidate in November 2019. Qualitative approach was conducted to analyze the types and social factors of code mixing. Observation method with writing technique used to collect the data. Data reduction, data display and drawing conclusion are the process of analysis technique. To classify and explain the social factors of code mixing, Musyken’s typology of code mixing (2000) and Kim’s theory of reasons and motive of mixing code (2006) were used. From the finding, there was found that three types of code mixing such as insertion, alternation and congruent lexicalization. Insertion type of code mixing was dominated in BKN’s twitter status, followed by congruent lexicalization and the last is alternation. Most of mixing code in twitter status related with particular topic about computer technical support, online registration system, and requirements of civil servant candidates. However, there are other code-mixing factors; participant roles and relationships and internal factors (quotation).